Enhancing the Collegian of Early Childhood Critical Thinking Skills Through Development of Textbook Integrated STEM Learning Model - Irawan, Ferry; Rafi'y, Muh; Harahap, Dharma Gyta Sari; Hanip, Rival; Bahri HS, Syamsul (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2025)
The research aims to develop textbooks that are integrated with Science, Technology, Engineering, Mathematic (STEM) in training collegian critical thinking skills as a basic skill to be able to express ideas that have originality. The research carried out is classified as research and development using the ADDIE model which consists of analysis, design, development, implementation and evaluation. The population is early childhood education collegian consisting of two different classes with a total population of 118 collegian. The results shown that in two different classes regarding the urgency of statistics textbooks using the STEM approach and refers to the STEM Critical Thinking rubric and is able to fulfill the achievement of critical thinking skills indicators. Based on the research conducted it was concluded that the critical thinking indicators that integrates the STEM approach model which is supported by interesting features provided in textbooks which make it easy for students to access any information independently and able to make students think critically in learning activities. The implication to the study show that STEM-based statistics textbooks help students to understand educational statistics material thoroughly with the help of various innovative features used in the textbooks